ANALISIS PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KENYAMANAN, DAN PERSEPSI KEMANFAATAN TERHADAP MINAT MENGGUNAKAN E-COMMERCE - Ardian Saputra; Algifari (Jurnal Ekonomi Dan Bisnis, 2022)
This study aims to examine the effect of perceived ease of use, perceived enjoyment, and perceived usefulness on the interest in using e-commerce in Jambi province. This study also identifies the importance and performance of perceived ease of use, perceived enjoyment, and perceived usefulness to create interest in using e-commerce. The sample used in this study amounted to 98 respondents. The research model is the Partial Least Square (PLS) and Importance-performance Map Analysis (IPMA) models. The results showed that perceived ease of use and perceived enjoyment have a positive effect on interest in using e-commerce. Perceived usefulness has no effect on interest in using e-commerce. The perceived ease of use and perceived enjoyment of using e-commerce are considered high performing, but low in importance to interest in using e-commerce. While usefulness is considered low performing, but respondents have high importance in usefulness.